Internal Control as a Mediator in the Quality of Financial Information at Education Foundations - Safa Azora, Aura; Hendra Hertanto, Ronny; Poernamawatie, Fahmi; Made, Anwar; Saharana, Anindya (Research Horizon, 2025)
The preparation of quality financial reports is essential for ensuring accountability and transparency in educational institutions. This study aims to empirically test whether internal control can mediate the effects of financial accounting literacy and human resource competence on the quality of financial information. The research was conducted in 48 educational foundations overseeing at least two schools, from elementary to high school. Data were collected through questionnaires and analyzed using the SEM-PLS method with Smart PLS 4 software, covering descriptive statistics, validity and reliability tests, R-Square, path coefficients, and hypothesis testing. Results show that accounting literacy significantly improves the quality of financial information, and internal control mediates the relationship between accounting literacy and financial statement quality. However, internal control does not mediate the effect of human resource competence, which also shows no significant direct impact. These findings highlight the importance of strengthening accounting literacy and internal control systems to enhance the reliability and accountability of financial reports in educational foundations.